Hierarchical Morphology and Formation Mechanism of Collision Surface of Al/Steel Dissimilar Lap Joints via Electromagnetic Pulse Welding - Puquan Wang; Daolun Chen; Yunqi Yan; Xinwei She; Bo Feng; Yang Ran; He Peng; Dongyang Li; Xianquan Jiang (Metals, 2021)
The aim of this study was to characterize detailed microstructural changes and bonding characteristics and identify the formation mechanism of collision surface of Al6061–Q355 steel dissimilar welded joints via electromagnetic pulse welding (EMPW). The collision surface was observed to consist of five zones from the center to the outside. The central non-weld zone exhibited a concave and convex morphology. The welding-affected zone mainly included melting features and porous structures, representing a porous joining. The secondary weld zone presented an obvious mechanical joining characterized by shear plateaus with stripes. The primary weld zone characterized by dimples with cavity features suggested the formation of diffusion or metallurgical bonding. The impact-affected zone denoted an invalid interfacial bonding due to discontinuous spot impact. During EMPW, the impact energy and pressure affected the changes of normal velocity and tangential velocity, and in turn, influenced the interfacial deformation behavior and bonding characteristics, including the formation of micropores which continued to grow into homogeneous or uneven porous structures via cavitation, surface tension, and depressurization, along with the effect of trapped air.